PENGARUH EXPERIENTIAL MARKETING, BRAND IMAGE, PRICE PERCEPTION TERHADAP CUSTOMER SATISFACTION PADA KONSUMEN STARBUCKS RESERVE DEWATA - Sari, Putri Sofiah; Respati, Ni Nyoman Rsi; Yasa, Ni Nyoman Kerti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.02.TAHUN.2023DO - 10.24843/EEB.2023.v12.i02.p18, 2023)
The development of culinary industry in Indonesia is getting promising. One of business that focuses on selling beverages is a coffee shop.  Coffee shop is a place that offers beverage with variety of coffees. Starbucks Reserve Dewata is a new innovation from Starbucks which was inaugurated in 2019 and became the largest Starbucks Outlet in Southesast Asia. It is intended for people who understad coffee and interest to try a deeper experience on enjoying coffee. This study aims to examine and explain the effect of experiential marketing, brand image, and price perception on customer satisfaction at Starbucks Reserve Dewata consumers. This research was conducted in Denpasar city with 150 respondents using Google forms questionnaire. Determination of the sample using a non-probability sampling model with purposive sampling technique. The data analyzed using multiple linear regression. The results of this research indicate that all hypotheses are accepted. Experiential marketing has a significant and positive effect on customer satisfaction. Brand image has a significant and positive effect on customer satisfaction. Price perception has a significant and positive effect on customer satisfaction